2021
DOI: 10.3390/agronomy11040808
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Effect of Deficit Irrigation and Sowing Methods on Weed Dynamics and System Productivity of Maize–Cowpea Sequence on Vertisols

Abstract: The aim of this study was to explore the effect of sowing methods and deficit irrigation on weed dynamics, yield and water-use efficiency (WUE) of the maize–cowpea system during the summer and monsoon seasons, respectively. The field experiment was carried out for two years (2015 and 2016) using a split design with three replicates under irrigated (maize) and rainfed (cowpea) conditions on vertisols of a semi-arid region. Treatments included three sowing methods [i.e., broad bed and furrow (BBF), corrugated fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…A deficit moisture regime might have reduced the water uptake of weeds (Abouziena et al, 2014), as reported in this study (Figure 2c,3b,and 4b). Similarly, accumulation of dry weight of weed increased with improved soil moisture availability (Halli et al, 2021), as observed in this study (Figure 2c,3b,and 4b). Furthermore, in the peanut deficit, the irrigation from 100 to 40% declined by 25.66% weed dry weight (El-Metwally et al, 2020).…”
Section: Effect Of Water Regimes On Plant Growth and Tubersupporting
confidence: 84%
See 4 more Smart Citations
“…A deficit moisture regime might have reduced the water uptake of weeds (Abouziena et al, 2014), as reported in this study (Figure 2c,3b,and 4b). Similarly, accumulation of dry weight of weed increased with improved soil moisture availability (Halli et al, 2021), as observed in this study (Figure 2c,3b,and 4b). Furthermore, in the peanut deficit, the irrigation from 100 to 40% declined by 25.66% weed dry weight (El-Metwally et al, 2020).…”
Section: Effect Of Water Regimes On Plant Growth and Tubersupporting
confidence: 84%
“…Increasing the deficit irrigation level drastically reduced EI, FEP (Figure 1b-c) and growth parameters (Figure 2, 3, 4). (Halli and Angadi, 2017) and (Halli et al, 2021) reported that appropriate moisture deficit is a viable option to suppress the weed and reduce water losses. Deficit irrigation of 24 to 40% less water can maintain productivity by suppressing weed competition (Coolong, 2013).…”
Section: Effect Of Water Regimes On Plant Growth and Tubermentioning
confidence: 99%
See 3 more Smart Citations